Parabrachial calcitonin gene-related peptide neurons sex-specifically modulate behavior in anxiety assays during alcohol withdrawal - Van Doorn, C. E.; Tyree, J. B.; Jaramillo, A. A. (Frontiers in Pharmacology, 2026)
Parabrachial nucleus (PBN) neurons expressing Calcitonin Gene-Related Peptide (CGRP) modulate fear- and anxiety-like behavior. It is unknown if PBN(CGRP) neurons play a role in anxiety during withdrawal from alcohol or after repeated stress. First, to investigate the anxiogenic role of activating PBN(CGRP) neurons in naïve conditions, CalcaCRE female and male mice expressing CRE-dependent hM3D (Gq) DREADDs in the PBN were tested on the elevated plus maze (EPM). PBN(CGRP) neurons drive phasic activity in the bed nucleus of the stria terminalis (BNST) that synchronizes to anxiety-like behavior. Therefore next, a transsynaptic anterograde AAV-based strategy was used in C57BL/6J female and male mice to activate BNST neurons innervated by the PBN projections (BNSTPBN) during EPM. Additionally, the quantity of PBN(CGRP) neurons and CGRP-innervated BNST cells was measured in experimentally-naïve CGRP-DTRGFP female and male mice, to investigate baseline sex-differences. Next, to investigate the impact of PBN(CGRP) inhibition on anxiety-like behavior following chronic intermittent ethanol vapor exposure (CIE), CalcaCRE female and male mice expressing CRE-dependent hM4D (Gi) DREADDs in the PBN were tested in EPM during acute withdrawal. Additionally, mice were exposed to repeated forced swim stress (FSS) paired with PBN(CGRP) inhibition followed by testing in the novelty suppressed feeding task (NSFT), to investigate the role of PBN(CGRP) on anxiety-like behavior after stress in protracted withdrawal. Activating PBN(CGRP) or BNSTPBN neurons did not change behavior in EPM in either sex. Total PBN(CGRP) and CGRP-innervated BNST cells did not differ between females and males. In acute withdrawal, inhibiting PBN(CGRP) neurons sex-specifically decreased total distance travelled and average speed in EPM. In protracted withdrawal, inhibiting PBN(CGRP) neurons during FSS disrupted the increase in immobility across sessions in females with no effect in males. A history of inhibiting PBN(CGRP) neurons during FSS increased anxiety-like behavior during NSFT, with implications for decreased motivation. Altogether, the data report that in alcohol withdrawal females and males differentially respond to PBN(CGRP) manipulations albeit they are both sensitive to the negative affect induced by repeated PBN(CGRP) manipulations during stress.